2015
DOI: 10.14393/bj-v31n4a2015-26185
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhization stimulant based in formononetin associated to fungicide and doses of phosphorus in soybean in the cerrado

Abstract: Arbuscular mycorrhizal fungi (AMF) are obligatory biotrophics, which complicates the feasibility of producing inoculants. Thus, the discovery of substances capable of stimulating mycorrhizal colonization, like the isoflavone formononetin emerges as a promising alternative to explore the benefits of AMF native soil in extensive crops system. The aim of this study was evaluate the application of the isoflavone formononetin (7-hydroxy-4'-methoxy isoflavone) andfungicide via seed in Cerrado soil in no-tillage syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 21 publications
5
18
0
1
Order By: Relevance
“…Different responses were also observed with the use of mycorrhizal stimulating in other studies (Novais & Siqueira 2009, Cordeiro et al 2015. However, the mycorrhizal colonization by native arbuscular mycorrhizal fungi was stimulated using the mycorrhizal stimulant (Cordeiro et al 2015).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Different responses were also observed with the use of mycorrhizal stimulating in other studies (Novais & Siqueira 2009, Cordeiro et al 2015. However, the mycorrhizal colonization by native arbuscular mycorrhizal fungi was stimulated using the mycorrhizal stimulant (Cordeiro et al 2015).…”
Section: Resultsmentioning
confidence: 69%
“…However, the mycorrhizal colonization by native arbuscular mycorrhizal fungi was stimulated using the mycorrhizal stimulant (Cordeiro et al 2015). This fact becomes important for the Brazilian Savannah region, for mycorrhizal plants have increased resistance to biotic (pests and diseases) and abiotic (water) stress, as several studies have shown (Novais & Siqueira 2009, Ferreira et al 2012, Cordeiro et al 2015.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This crop has high economic and social importance in Brazil, the greatest soybean producer worldwide. In Brazil, soybean is predominantly cropped in soils characterized by low availability of N and P, making these nutrients the main limiting factors to the growth and agricultural productivity of soybean (CORDEIRO et al, 2015;YAMADA;ABDALLA, 2004). Because soybean can form symbiosis with N 2 -fixing bacteria belonging to the genus Bradyrhizobium, the plant demand for N may be completely supplied by biological nitrogen fixation SIQUEIRA, 2006).…”
Section: Introductionmentioning
confidence: 99%